Why do postgraduate students commit plagiarism? An empirical study - Apatsa Selemani (International Journal for Educational Integrity, 2018)
Abstract The study investigated postgraduate students’ knowledge of plagiarism, forms of plagiarism they commit, the reasons they commit plagiarism and actions taken against postgraduate students who plagiarise at Mzuzu University in Malawi. The study adopted a mixed methods approach. The quantitative data were collected by distributing questionnaires to postgraduate students and academic staff whereas qualitative data were collected by conducting follow-up interviews with some academics, an assistant registrar and assistant librarian. The study found that despite students reporting that they had a conceptual understanding of plagiarism, the majority of them reported that they had intentionally and unintentionally committed plagiarism, mainly due to pressure for good grades (86.7%), laziness and poor time management (84.9%), and lack of good academic writing skills (84.9%). The study also established that prevalent forms of plagiarism admitted (by students) and reported (by academic staff) to have been committed included lack of proper acknowledgement after paraphrasing (69.8%), summarising (64.1%) and using quotation marks (56.6%). The study further found that the common sanctions applied by academics include giving a warning and asking the student to re-write the plagiarised work. The study recommends that Mzuzu University should carry out awareness campaigns about the negative effects of plagiarism, targeting postgraduate students; and should introduce advanced academic writing skills training for postgraduate students.